Suspender Replacement Method for Long-Span Concrete-Filled Steel Tubular Arch Bridges and Cable Force Measurement Based on Frequency Method - Yulin Deng; Luming Deng (Advances in Civil Engineering)
The suspenders on the sides of an arch bridge are highly vulnerable to damage caused by traffic load and environmental corrosion. To accurately estimate the cable force of suspenders, herein, we analyse the influencing factors through a suspender tension test based on the principle of suspender vibration. The frequency of each suspender of the bridge is evaluated using the frequency method. By combining the cable force data measured directly and the measured suspender frequency, the formulas for calculating the cable forces of long and short suspenders are fitted, and a reasonable estimation method for the calculated length of short suspenders is provided. The formulas are verified through application to a CFST arch bridge. Results indicate that the proposed formula effectively considers the influence of the sleeve on the overall calculated length of the suspender. The formula calculates the suspender cable force with higher accuracy, proving its suitability for engineering use.